Folk Medicine, Folk Healing - Mustafa SEVER (Gazi Akademik Bakış)
Folk medicine and folk healing may be defined codified, regulated, taught openly and practised widely, and benefit from thousands of years of experience. On the other hand, it may be highly secretive, mystical and extremely localized, with knowledge of its practices passed on orally. Folk medicine and traditional medical practices emerged as a result of the reactions of primitive men against natural events and their ways of comparing and exchanging the medical practices of relevant communities with their own practices. Magic played an important role in shaping the practices. Folk medicine is the solutions developed by societies against material and moral disorders starting from the mythic period until today. Folk healer, on the other hand, is the wisest and the most respectable person in the society, in terms of materiality and morale. This person has the power of identifying and curing the diseases, disorders, consequently the origin of these diseases and disorders, and the skill of using various drugs for the treatment of the diseases and disorders or applying the practices with the help of information and practices acquired from the tradition. The Turks having rich and deep rooted culture. The Turkısh folk medicine and folk healing that contain rich cultural structure in themselves survive until today by being fed by different sources. Before Islam, the Turks used to believe that there were white and black possessors, ancestors’ spirits (arvaks) and their healthy and peaceful life depended on getting on with these spirits. They also believed that diseases were caused when they could no more keep in with possessors and spirits, or when they offended and annoyed them. In such an environment of belief, the visible diseases caused by material reasons were generally cured with products obtained from plants, mines and animals in the region or drugs that were made out of their combinations. On the other hand, in invisible diseases associated with spirits and possessors, on the other hand, the treatment was undertaken by kams and they removed the disorder with the help of practices called “kamla-“, which involved various magics and bewitcheries. These features of kams occasionally coincide with the features of people known as “ocak” or “ocakli” in many regions of Anatolia. According to the information given by ocak/ocakli people whom we met in various regions, an ocak or ocakli person does not demand a certain fee after or before her/his practices and treatments; thus, there is no bargain between the patient and the ocakli. In this study, folk medicine and folk healing in Turkish culture will be introduced and evaluated.